The Relationship Between The Implementation Of Standard Inpatient Care (Kris) And Service Quality On Patient Satisfaction At Raa Soewondo Pati Regional General Hospital - Ingrid Novi Aryani Ingrid Novi Aryani; Rusnoto Rusnoto; Ahmad Farid (International Journal of Health Engineering and Technology, 2026)
Improving equitable inpatient service quality remains a critical challenge in Indonesia following the implementation of the Standard Inpatient Care Class policy. This study examined the relationship between policy implementation, service quality dimensions, and patient satisfaction at RAA Soewondo Pati Regional Hospital. A quantitative cross-sectional design was employed involving 150 inpatients selected through simple random sampling from a population of 235 standard-class patients. Data were collected using a structured SERVQUAL questionnaire covering reliability, responsiveness, assurance, empathy, tangibles, and overall satisfaction. Descriptive statistics, Chi-square tests, and Spearman rank correlation were applied. Results showed that most respondents rated service quality positively: reliability (90.0%), responsiveness (91.3%), assurance (80.7%), empathy (85.3%), and tangibles (79.3%). Overall, 87.3% of patients reported satisfaction. Chi-square analysis indicated that only age was significantly associated with satisfaction (p < 0.001). Spearman analysis confirmed a positive correlation between age and satisfaction (rs = 0.233; p = 0.004) and between tangibles and satisfaction (rs = 0.201; p = 0.014). Reliability, responsiveness, assurance, empathy, and gender were not significantly related to satisfaction (p > 0.05). The findings suggest that the policy has effectively improved structural and physical aspects of care, while interpersonal service dimensions remain relatively uniform. Hospitals should prioritize facility enhancement alongside communication and empathy training to further improve patient satisfaction.